Controle de microrredes CA: estudo da regulação de frequência e tensões - Carvalho, Henrique Tannús de Moura (2019)
This work focuses on presenting a study about the control of AC microgrids, mainly addressing the secondary control for frequency and voltage regulation during isolated (islanded) operation. The main issues regarding the control of AC microgrids are discussed through a bibliographical review, focusing on distributed and hierarchical strategies, presenting the objectives, mains limitations and advantages of the most relevant techniques. As the most important contribution, is the proposal and study, by means of several computational simulations, of a secondary control to regulate the frequency and voltages of the microgrid. The main features of the strategy are: complete decentralization; simplicity of implementation, tuning and mathematical modeling. In addition, are presented and validated with computational simulations: a strategy for steady state compensation of the voltage drop at the virtual impedances, without cancelling its dynamic contribution; a simple modification in the implementation of the proposed secondary control for proper operation in systems with generating units of distinct nominal power ratings. Although the electric power quality in the microgrid for islanded operation, with respect to frequency and voltages amplitude, is the central axis of this work, the problem of power sharing between generating units is discussed at several points throughout the text, because of its great importance and strong relation with the technique adopted for primary and secondary control. The studied secondary control did not caused problems for the power sharing, and even reduced the deviations in the reactive power sharing in several analyzed cases.